Rationality and Humour In Counselling - Klein, Joel P. (Canadian Journal of Counselling and Psychotherapy, 2012)
Although frequently employed by counsellors on a non-systematic basis, humour is a relevant therapeutic variable in need of theoretical explication. The role of humour is demonstrated by contrasting it with the function of reason, and some of the psychological mechanisms of humour are explained. Because the author draws upon examples from his own counselling experience, brief discussions are made into related topics such as the new diagnostic category of "identity crisis", the understanding of counsellor training as a form of operant conditioning, and the role of theory in counselling.